2015
DOI: 10.1016/j.amjmed.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Combined Internal Medicine–Pediatrics Workforce

Abstract: AAIM is the largest academically focused specialty organization representing departments of internal medicine at medical schools and teaching hospitals in the United States and Canada. As a consortium of five organizations, AAIM represents department chairs and chiefs; clerkship, residency, and fellowship program directors; division chiefs; and academic and business administrators as well as other faculty and staff in departments of internal medicine and their divisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Our results are in line with prior surveys outlining that a majority of med-peds physicians practice both adult and pediatric hospital medicine [ 2 , 3 , 10 ]. The growing number of practicing med-peds hospitalists demands a better understanding and distinction of the unique needs of these doctors in order to better identify career opportunities and areas for improvement.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are in line with prior surveys outlining that a majority of med-peds physicians practice both adult and pediatric hospital medicine [ 2 , 3 , 10 ]. The growing number of practicing med-peds hospitalists demands a better understanding and distinction of the unique needs of these doctors in order to better identify career opportunities and areas for improvement.…”
Section: Discussionsupporting
confidence: 92%
“…This survey describes the institutional characteristics and practice patterns of actively practicing med-peds hospitalists. An estimated 100 new med-peds hospitalists join the workforce each year [ 9 ], with an estimated total number of practicing med-peds hospitalists in 2015 at around 350-400 total [ 2 ]. Based on the reported numbers of hospitalists per group from this study (approximately 250 on a low estimate), this survey encompasses a large proportion of the estimated total of those practicing med-peds hospitalists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study of medicine-pediatrics physicians revealed that although they are likely to include pediatric care in their practices, the contribution of combined internal medicine and pediatrics physicians to pediatric primary care has decreased. 60 In fact, more recent graduates of combined internal medicine and pediatrics training programs are more likely to become specialists and to identify as hospitalist physicians. In addition, we did not include surgeons who provide care to pediatric patients.…”
Section: Limitationsmentioning
confidence: 99%